2014
DOI: 10.1186/1556-276x-9-334
|View full text |Cite
|
Sign up to set email alerts
|

Indium droplet formation in InGaN thin films with single and double heterojunctions prepared by MOCVD

Abstract: Indium gallium nitride (InGaN) samples with single heterojunction (SH) and double heterojunction (DH) were prepared using metal-organic chemical vapor deposition. SH has a layer of InGaN thin film (thicknesses, 25, 50, 100, and 200 nm) grown on an uGaN film (thickness, 2 μm). The DH samples are distinguished by DH uGaN film (thickness, 120 nm) grown on the InGaN layer. Reciprocal space mapping measurements reveal that the DH samples are fully strained with different thicknesses, whereas the strain in the SH sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 62 publications
2
5
0
Order By: Relevance
“…They belong to InGaN and GaN crystal, respectively. While the extra characteristic peak located at the 2θ = 32.8°has been verified to come from the In droplet [16,17]. So we can make a conclusion that the quantum dots we observed on the InGaN surface with the two-step cooling process is the In droplet.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…They belong to InGaN and GaN crystal, respectively. While the extra characteristic peak located at the 2θ = 32.8°has been verified to come from the In droplet [16,17]. So we can make a conclusion that the quantum dots we observed on the InGaN surface with the two-step cooling process is the In droplet.…”
Section: Resultssupporting
confidence: 57%
“…Previous studies have shown that there exist three different states of In atoms in the process of InGaN layer growth [16,17]. The first one is the In atoms in InGaN alloy crystal lattice, which is the main part and the target product of InGaN layer growth; the second one is the InN alloy which always appears on the surface of the InGaN layer; and the third one is the In droplet which may appear in some special growth condition.…”
Section: Resultsmentioning
confidence: 99%
“…We confirm that the quantum wells are grown in the semi-polar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) face direction. Quantum wells on the semi-polar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) face less lattice mismatches between InGaN and GaN, as reported by previous studies [29][30][31][32][33][34][35][36]. We believe that less lattice mismatches result in better-quality GaN nanorods and InGaN/GaN quantum wells.…”
Section: Tem and Hrtem Measurementssupporting
confidence: 55%
“…EL spectra of the c -LED just coincide with the lower energy shoulder of that for the m -LED. Both carrier localization effect [2123] and QCSE [38] in the c -LED contribute to luminescence. The large difference of EL peak positions for the m -LED from that for the c -LED can’t be discussed by only one effect.…”
Section: Resultsmentioning
confidence: 99%